If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n + 29 = 0 Reorder the terms: 29 + 9n = 0 Solving 29 + 9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + 9n = 0 + -29 Combine like terms: 29 + -29 = 0 0 + 9n = 0 + -29 9n = 0 + -29 Combine like terms: 0 + -29 = -29 9n = -29 Divide each side by '9'. n = -3.222222222 Simplifying n = -3.222222222
| -4(3w+2)-w=31 | | -4(3w+3)-w=31 | | 2x^2+7x-9=x^2-x | | 2x-x=10 | | 2x^3=7x^2 | | -44+x=25 | | 4(10x)+3=15 | | 3(r-9)=8r-27 | | -5x/9-6-9 | | (x+2y)dx+y*dy=0 | | (x+12)(x-5)=x^2+31 | | 3r+5+r^2=0 | | 2x^2+300=0 | | 14=8+j | | -5x=20-20 | | 10b-3b-18=b+26-5b | | 3-x=7x+6 | | 10=1.8x-x | | 68-2n=0 | | 3x-y+2x+7y=90 | | m(x)=-x^2+4 | | 5x=55+5 | | (2x-4)+9i=8+3yi | | 6x+28=2x | | 4/2-8i | | 4t-1=9-t | | 4n-16= | | (B+4)7=-3 | | 3x-25=75 | | 18+15H=90 | | -43-x=-60 | | -43-x=60 |